CLINICAL AND BACTERIOLOGICAL PECULIARITIES OF THE ACUTE OTITES MEDIA IN CHILDREN OF 0-5 YEARS OF AGE: PROVISIONAL DATA - A. L. Perova; A. A. Ruleva; S. S. Belanov; S. M. Kharit; S. V. Sidorenko (Union of pediatricians of Russia, 2012)
Analysis of clinical peculiarities and etiological structure of otites in 150 children of 0-5 years of age hospitalized with the diagnosis «acute otitis media», which was proved otoscopically and at paracentesis, was conducted. Fluid obtained at paracentesis was examined bacteriologically - in 128 cases, by the PCR method - in 129 cases. 121 disease cases were etiologically identified, pneumococcus was singled out in 93 children (76.9%), as the only causative agent - in 31.4%, in combination with other pathogens - in 45.5%. Pneumococcal serotyping showed that the singled out strains correspond to the pneumococcal infection conjugate vaccines registered in Russia, which is a reason for cohort immunization of small children.